EUTANASIA DALAM PANDANGAN AL-QUR’AN: (Telaah atas Ayat-Ayat Bunuh Diri dengan Pendekatan Tafsir Maqāshid) - habieb Habieb; Yusran Djama (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2022)
Humans never know the time of their death because life and death are Allah's provisions. However, death has causes such as disease, war, etc. This fact proves that Allah does not act arbitrarily on His creatures. Ironically, there are deaths caused by suicide both by self and by medical procedures for certain reasons, namely euthanasia. Suicide is mentioned four times in the Qur'an surah al-Nisā': 29, al-Baqarah: 53, al-Baqarah: 85, and al-Nisā': 66. This research used a qualitative approach, the library research method by collected several literature sources such as books, journals, and previous scientific research that discussed euthanasia. The Maqāsidy Tafsir method was applied to study verses regarding euthanasia to derive wisdom from a verse. The results pointed out that the verses of suicide from the Tafsir Maqāsid perspective provide two understandings, first is the prohibition of suicide in surah al-Nisā': 53 and second is the suicide order in surah al-Baqarah: 53. The suicide command is in the context of repentance, as happened to the people of the Prophet Mūsa. The suicide prohibition is the wisdom of Allah to signify His majesty that only Him has the right to bring humans to life and death. Eventually, this verse also has a contradiction with the euthanasia case.